2015
DOI: 10.2298/mpns1512387j
|View full text |Cite
|
Sign up to set email alerts
|

The role of nutrition in caries prevention and maintenance of oral health during pregnancy

Abstract: Preserving of oral health during pregnancy is predominantly influenced by the following factors: 1) healthy diet, 2) oral hygiene, 3) patients' education, 4) regular control of oral health, 5) appropriate organization of dental services and 6) community engagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
(23 reference statements)
0
7
0
2
Order By: Relevance
“…Any attempt to eliminate this barrier is of high importance, since it is directly related to the mother's quality of life, minimizing the chances of oral pain, psychological discomfort, physical and psychological disability, social disability and handicap 6,51 . Moreover, the maintenance of good oral health during pregnancy depends on healthy diet and oral hygiene 52 and health literacy (we will discuss below) is the key to that.…”
Section: Major Findingsmentioning
confidence: 99%
“…Any attempt to eliminate this barrier is of high importance, since it is directly related to the mother's quality of life, minimizing the chances of oral pain, psychological discomfort, physical and psychological disability, social disability and handicap 6,51 . Moreover, the maintenance of good oral health during pregnancy depends on healthy diet and oral hygiene 52 and health literacy (we will discuss below) is the key to that.…”
Section: Major Findingsmentioning
confidence: 99%
“…Furthermore, some studies have shown a high prevalence of tooth decay among pregnant women [Radnai et al, 2007;Vergnes et al, 2013]. This may be related to some behavioral changes that can occur during pregnancy, such as difficulties to performing good oral hygiene and increased sugar consumption, leading to higher bacterial plaque scores [Vergnes et al, 2013;Amin and ElSalhy, 2014].To preserve oral health during pregnancy, a healthy diet and proper oral hygiene are essential [Jevtić et al, 2015]. However, regardless of all possible adverse outcomes and the importance of seeking preventive care in this condition, studies have shown rates as high as 56-74% in pregnant women who have reported no dental visits [Boggess et al, 2010;Marchi et al, 2010;Vergnes et al, 2013].…”
mentioning
confidence: 99%
“…It is of utmost importance to start the prevention of oral health as early as possible [17], in order to ensure the prevention of oral health by reliable effects [18,19], which is defined by the dental health care quality parameters [20]. Great importance in prevention is to organize dental services and social engagement [21].…”
Section: Discussionmentioning
confidence: 99%